Growth-promoting rhizobacteria from Guarianthe skinneri (Orchidaceae). - Aguilar Diaz, Trinidad (2018)
The Guarianthe skinneri orchid is included in NOM-059-ECOL-2010, Mexico standard as an endangered species. In order to study PGPR (promoting growth plant rhizobacteria) from this orchid, 10 roots were collected from different plants to isolate bacteria associated with the roots, which were analyzed by in vitro tests such as: production of AIA, nitrogen fixation, interaction with the mycorrhizal fungus Thanatephorus sp. strain RG26 and phosphate solubilization. We obtain 71 bacterial isolates, 10 strains of them were characterized by sequencing with the 16d rDNA marker identifying six bacteria: Sphingomonas sp. Sinorhizobium sp. Bacillus sp. Nocardia cerradoensis, Bacillus megaterium and Burkholderia phytofirmans. We observed that the bacterium Sinorhizobium sp. produced a greater amount of AIA (69.189 μg/ml) and Bacillus sp. performed greater acetylene reduction (10.251 nmol cultivo/96h). In the interactions of the bacteria and the fungus RG26, four categories were presented (extremely positive, positive, antagonism 50-50 and inhibition). In relation to the solubilization of phosphate, Burkholderia phytofirmans presented higher IS after 48 and 96 hr with an IS of 3.11 and 3.48, respectively. The results indicate that Bacillus sp. it could have the best characteristics to promote the development of the G. skinneri orchid by inoculating seeds and seedlings.